The literary Freud - Meisel, Perry (New York, NY : Routledge, 2007)
Meisel argues that Freud's texts are properly literary, and casts Freud as both literary theoretician and practitioner. After an introductory reception history of Freud as literature, Meisel provides a series of close readings of Freud's major texts that take literary representation as their central focus.
Includes bibliographical references and index.
Keywords: Freud, Sigmund, 1856-1939; Psychoanalysis and literature